2009
DOI: 10.1007/s00428-009-0837-4
|View full text |Cite
|
Sign up to set email alerts
|

Nodular pattern of bone marrow infiltration: frequent finding in immunosuppression-related EBV-associated large B-cell lymphomas

Abstract: Different patterns of bone marrow (BM) infiltration by diffuse large B cell lymphomas (DLBCL) have been described. A pure nodular pattern is uncommon, and the pathologic features, as well as the clinical correlates of DLBCL manifesting this pattern in the BM have not been well characterized. We evaluated BM biopsies involved by large B cell lymphomas diagnosed at our institute over an 11-year period to assess the morphology, phenotype, cytogenetic abnormalities, and clinical features of cases associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…It has been confirmed that immune deficiency is one of the main reasons for pneumonia recurrence (17). Seeing that immune deficiency was involved in tumorigenesis and development of DLBCL (18,19), patients with pneumonia at onset were more likely to experience pneumonia after immunochemotherapy. Our study showed that the risk of pneumonia was 9.54-fold higher in this special population.…”
Section: Discussionmentioning
confidence: 97%
“…It has been confirmed that immune deficiency is one of the main reasons for pneumonia recurrence (17). Seeing that immune deficiency was involved in tumorigenesis and development of DLBCL (18,19), patients with pneumonia at onset were more likely to experience pneumonia after immunochemotherapy. Our study showed that the risk of pneumonia was 9.54-fold higher in this special population.…”
Section: Discussionmentioning
confidence: 97%